Phylogenetic analysis of the Neotropical Pristimantis leptolophus species group (Anura: Craugastoridae): molecular approach and description of a new polymorphic species - Rivera-Correa, Mauricio; Jiménez-Rivillas, Carlos; Daza, Juan M. (Zootaxa, 2017)
Pristimantis, distributed throughout the New World tropics, is the most speciose vertebrate genus. Pristimantis presents an enormous morphological diversity and is currently divided into several demonstrably non-monophyletic phenetic species groups. With the purpose of increasing our understanding of Pristimantis systematics, we present the first phylogenetic analysis using molecular evidence to test the monophyly and infer evolutionary relationships within the Pristimantis leptolophus group, an endemic group of frogs from the highlands of the Colombian Andes. Our phylogenetic reconstruction recovers the group as monophyletic with high support, indicating general concordance between molecular data and morphological data. In addition, we describe a new polymorphic species lacking conspicuous tubercles, a regular attribute among species of the P. leptolophus species group and endemic from the Páramo de Sonsón complex (Antioquia, Colombia). The phylogenetic position of the new species is inferred and other systematic implications in the light of our results are discussed.